2012
DOI: 10.1515/jpem-2012-0090
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoimmunity in 72 children with type 1 diabetes mellitus: relationship with pancreatic autoimmunity and child growth

Abstract: The aim of this study was to assess the association between pancreatic and thyroid autoimmunity (TA) and determine impact of thyroid antibodies on statural growth. Seventy-two children with type 1 diabetes mellitus (TIDM) and no clinical evidence of thyroid disorders were evaluated: glycated haemoglobin (A1c), thyroid peroxidase antibodies (TPOAb), glutamic acid decarboxylase antibody (GADA), tyrosine phosphatase antibodies (IA2A), and thyroid-stimulating hormone (TSH). The score of standard deviation for heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
5
7
0
Order By: Relevance
“…A similar prevalence of GADA positivity (47 %) was observed in a study performed on insulin-treated type 2 diabetes mellitus inpatients, whereas only 10 % of the patients not treated with insulin were positive for GADA [30]. TA based on TPOAb measurements displayed a prevalence of 28.8 % in our study; this result was higher than that for classical type 1 diabetes mellitus [31,32]. Few studies have examined TA among LADA patients [16,17,19,33].…”
supporting
confidence: 86%
“…A similar prevalence of GADA positivity (47 %) was observed in a study performed on insulin-treated type 2 diabetes mellitus inpatients, whereas only 10 % of the patients not treated with insulin were positive for GADA [30]. TA based on TPOAb measurements displayed a prevalence of 28.8 % in our study; this result was higher than that for classical type 1 diabetes mellitus [31,32]. Few studies have examined TA among LADA patients [16,17,19,33].…”
supporting
confidence: 86%
“…Many studies have demonstrated that several factors such as age, the female sex, duration of disease, and the presence of beta cell autoimmunity are associated with AIT in type 1 DM patients [ 9 , 10 , 13 , 20 - 22 ]. In our study, GADA positivity at the onset of type 1 DM was a predictor of AIT development.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid autoantibodies can be detected at the initial diagnosis or can be detected over time, after diagnosis [ 5 , 6 ]. Age at diagnosis, pubertal status, and the female gender have been associated with thyroid autoantibody in children and adolescents with type 1 DM [ 7 - 10 ]. In addition, recent studies have reported that the presence of glutamic acid decarboxylase antibodies (GADA) and human leucocyte antigen class II genes may influence the development or progression of AIT [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent extensive Ab screening study in patients with T1DM has raised awareness of the association of T1DM with organ-specific autoimmunity [29]. The reported prevalence of thyroid autoimmunity in young T1DM patients ranges between 3% and 50% [10,[30][31][32][33], while it is 3.4%-7% in the general paediatric population [34,35]. The association of T1DM and AITD is highly dependent on age, sex and ethnicity [36].…”
Section: Discussionmentioning
confidence: 99%